Stress fractures and knee injuries in runners - Hoch, A. Z.; Pepper, M.; Akuthota, V. (Physical Medicine & Rehabilitation Clinics of North America, 2005)
Running often can cause injuries to the knee as a result of kinetic chain dysfunctions. Addressing these dysfunctions in rehabilitation can prevent future injury. Stress fractures often occur in runners who engage in training errors. Female runners are particularly susceptible to stress fractures, especially in the setting of the female athlete triad. Proper identification and prevention of these injuries allows for athletes to return to running expeditiously.